Development of ICT-Based Islamic Religious Education Learning Media at MTs Muhammadiyah 15 Medan - Rusydi, M. Sani Hafiz; Setiawan, Hasrian Rudi; Hasibuan, Riki Naldi; Prasetyo, Afif Imran (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2025)
This study aims to develop an ICT-based Islamic Religious Education (IRE) learning media that is appropriate and engaging for students of MTs Muhammadiyah 15 Medan. The research method employed is Research and Development (RD) using a simplified Borg Gall model. The developed product is an interactive PowerPoint-based media integrated with materials, images, videos, and quiz-based evaluations. Instruments used include validation questionnaires from content and media experts, as well as student response questionnaires. Validation results indicated that the media is highly appropriate, with an average feasibility score above 85%. Student responses also showed high enthusiasm for the media, which was considered attractive, easy to use, and helpful in understanding the material. The study concludes that the developed ICT-based IRE learning media is highly suitable for classroom use and can enhance students' interest and comprehension.